Prevalence of genital and extragenital sexually transmitted infections among women of reproductive age with and without HIV in the Southern US: results from the study of treatment and reproductive outcomes - Nogueira, Nicholas F.; Beauchamps, Laura S.; Pan, Yue; Beato Fernandez, Paola; Rodriguez, Maria Gabriela; Kelsey, Gray; Raccamarich, Patricia; Sternberg, Candice A.; Westreich, Daniel; Kassaye, Seble G.; Topper, Elizabeth F.; Rana, Aadia; et al. (Frontiers in Medicine, 2025)
IntroductionSexually transmitted infections (STI) are highly prevalent among women of reproductive age (WRA) and increase the risk of HIV acquisition and transmission. However, the burden of extragenital STIs is understudied among WRA in the US. Estimates of disease are urgently needed among women living with (WWH) and without HIV (WWOH), to inform sex-specific screening guidelines.MethodsCross-sectional data from cisgender WWH and WWOH, ages 18–45 years, enrolled in the Study of Treatment and Reproductive Outcomes (STAR) from March 2021 to August 2023 at six Southern US sites was analyzed. Sociodemographic and behavioral assessments were performed using structured interviewer-administered questionnaires. Nucleic-acid amplification tests were performed, regardless of symptoms, on self-collected urine, rectal, and pharyngeal swabs to detect trichomoniasis, chlamydia, and gonorrhea. Sociodemographic characteristics and risk factors were compared by STI status and concordance between genital and extragenital STIs was examined.ResultsAmong the 543 participants, 55.2% WWH, mean age was 34.0 (SD ± 7.14) years old, most (72.5%) were non-Hispanic Black, 41.6% had multiple sexual partners, and 85.6% engaged in unprotected sex. Overall, 1.9% tested positive for genital chlamydia, 2.9% rectal chlamydia, 0.6% oropharyngeal chlamydia, 3.4% genital gonorrhea, 1.2% rectal gonorrhea, 1.3% oropharyngeal gonorrhea, and 12.2% trichomoniasis. Genital chlamydia was associated with rectal chlamydia (p < 0.001) but not oropharyngeal chlamydia; and genital gonorrhea associated with rectal (p < 0.001) and oropharyngeal (p = 0.0011) gonorrhea. Eight (11.1%) pregnant participants were diagnosed with at least one STI. Higher genital chlamydia risk was associated with women without healthcare provider visits in the past year [RR = 7.14, 95% CI (1.92, 25.00); p = 0.043]; while higher trichomoniasis risk was associated with lower educational attainment of high school or below [RR = 2.94, 95% CI (1.49, 5.88); p = 0.009] and an average monthly income of less than $1,500 USD [RR = 4.76, 95% CI (1.82, 12.5); p = 0.011]. HIV-status was not associated with genital or extragenital STIs.DiscussionPrevalence of genital, rectal, oral chlamydia (1.8%, 2.8%, and 0.6%) and gonorrhea (3.3%, 1.1%, and 1.3%), and genital trichomoniasis (11.4%) are high among WRA with and without HIV. The adverse impact for women’s reproductive health and HIV transmission highlights the importance of extragenital STI testing for women in areas of high prevalence of STIs in the US.